Pengembangan Model Penilaian Portofolio dalam Pembelajaran Matematika Berbasis Lesson Study di SMP - Sumardi, Sumardi (Jurnal VARIDIKA, 2016)
The objective of this study is to know deeply the implemantation of portofolio evaluation model in teaching learning mathematics based on lesson study. This qualitative research was done at three SMP Muhammadiyah schools at Sukoharjo residence, teachers and students as a subject of the study. Data were collected by interview, test, and documentation, then analysed by interactive model. The results are (1) the teachers of the three schools do not understand completely yet about of portofolio evaluation model in teaching learning mathematics based on lesson study, process of the development from planning (making lesson study until making portofolio); (2) at the stage doing, the teachers have done correctly as stated on Lesson Plan; (3) on the reflecting, the teachers have made the students active in learning.